Profiling and Quantification of Anthocyanins in Purple-Pericarp Sweetcorn and Purple-Pericarp Maize - Apurba Anirban; Hung T. Hong; Tim J. O’Hare (Molecules, 2023)
Purple-pericarp sweetcorn accessions, derived from crossing purple-pericarp maize with white shrunken2 sweetcorn, were assessed for differences in anthocyanin profile at both sweetcorn eating stage and at full kernel maturity. The ‘Tim1’ sweetcorn line developed a similar total anthocyanin concentration to its ‘Costa Rica’ parent when assessed at sweetcorn-eating stage. At full maturity it surpassed the purple maize parent, but this was mainly due to the presence of starch diluting the anthocyanin concentration of the latter. The anthocyanin/colour relationship was affected by both total anthocyanin concentration and the ratio of cyanidin- to pelargonidin-based anthocyanins. Malonylation of anthocyanins was also found to vary and did not appear to be linked with either cyanidin:pelargonidin ratio or total anthocyanin concentration. In addition, anthocyanin synthesis was affected by kernel maturity at harvest, with colour development increasing in conjunction with a progression of anthocyanin development across the kernel surface. Pigmentation was present in the aleurone, pericarp and vitreous endosperm of kernels of the purple-pericarp maize parent and purple-pericarp sweetcorn accessions when fully mature, but pigmentation was only apparent in the pericarp at sweetcorn-eating stage. Importantly for consumers, anthocyanin pigmentation covered almost the entire kernel surface at sweetcorn-eating stage.